Análise de desempenho no uso de pré-busca para distribuição de vídeo sobre redes P2P - Manola, Renan (2011)
Peer-to-Peer Video on Demand Systems have well stabilished its importance in recent years. Such consolidation is due to the high gains that may be archieved in terms savings in transmission bandwidth of the servers. In this work, we evaluate how this technology can enhance the gains for the transmission of continuous media over the Internet. To achieve this goal, the methodology relies on a packet-level simulation that has the ability to allow capturing different variables that regard the dynamics of the Internet, such as: full simulation of the TCP/IP stack, considerations on network topology and insertion of background traffic. In this simulation was implemented a video streaming P2P VoD algorithm and an algorithm that uses pre-fetching. Result analisys point out to a potential economy of the content server s upload bandwidth of up to 43% in a less idealized scenario than the results obtained on the base proposal that has archieved an economy of 73%. In terms of user s perceived video quality, this work indicates that the user s experience can be greatly degraded when using the UDP with background traffic, even with the economy of the server remaining constant. Still on the user's video quality perception, it was noted that, although the use of pre-fetching was proved beneficial to them, the key factor in best quality perceived was the choice of a proper transport layer.